Autonomic nervous system function in Huntington's disease. Issue 6 (1st June 2002) - Andrich, J; Schmitz, T; Saft, C; Postert, T; Kraus, P; Epplen, J T; Przuntek, H; Agelink, M W
Abstract : Objective: To investigate whether Huntington's disease (HD) affects autonomic nervous system (ANS) functioning. Methods: Twenty patients with HD who had positive genetic test results underwent standardised ANS function tests including sympathetic skin responses (SSRs) of the hands and feet, measurements of heart rate variability (HRV), both during five minutes of resting and deep respiration, and an orthostatic blood pressure test. Patients were classified according to the motor subscale of the unified Huntington's disease rating scale (UHDRS; mean (SD) score 26.4 (13.6)) and divided into two subgroups: UHDRS <25 points (early stages, E-HD) and UHDRS ≥25 points (mid stages, M-HD). Autonomic indices were compared with those obtained for a group of well matched healthy controls (n=60). Results: Overall, patients showed lower HRV indices than controls. Multivariate analysis with the independent factor of "group" (controls, E-HD, M-HD) showed a significant group effect on both the high frequency power ( F =4.32, p=0.017) and the coefficient of variation ( F =4.23, p=0.018), indicating a significant reduction in vagal modulation in the M-HD group. There was a shift in autonomic neurocardiac balance towards sympathetic predominance in the M-HD group compared with controls ( F =2.89, p=0.062). Moreover, we found an inverse correlation between the severity of clinical HD symptoms (assessed by the UHDRS) and the modulation of cardiovagal activity (p=0.028). Vagal dysregulation was present in two patients; one of them also showed a pathological blood pressure test and a latency prolongation in the SSRs of the hands. Two other patients had pathologically reduced SSR amplitudes. Only patients of the M-HD group were affected. Conclusion: Autonomic dysfunction is present even in the middle stages of HD and affects both the sympathetic and parasympathetic branch of the ANS.